New Images of Man - Selz, Peter (New York : The museum of Modern Art, 1959)
Appel, Karel ; Armitage, Kenneth ; Bacon, Francis ; Baskin, Leonard ; Butler, Reg ; Campoli, Cosmo ; César ; Diebenkorn, Richard ; Dubuffet, Jean ; Giacometti, Alberto ; Golub, Leon ; Greene, Balcomb ; de Kooning, Willem ; Lebrun, Rico ; Megarrell, James ; Müller, Jan ; Oliveira, Nathan ; Paolozzi, Eduardo ; Pollock, Jackson ; Richier, Germaine ; Roszak, Theodore ; Westermann H.C. ; Wotruba, Fritz
New Images of Man, The Museum of Modern Art, New York, 1959
boek